2021
DOI: 10.1016/j.ajem.2020.10.055
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in pregnancy and the puerperium: A review for emergency physicians

Abstract: Background Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is a novel virus responsible for causing the novel coronavirus disease of 2019 (COVID-19). Objective This article discusses the clinical manifestations of COVID-19 in pregnant patients, the effects of pregnancy on the course of COVID-19 disease, and the impact of COVID-19 on pregnancy outcomes. Discussion The physiological and mechanical changes associated with pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
3
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 47 publications
5
44
3
14
Order By: Relevance
“…A meta-analysis of 42 studies of pregnant patients found focal ground glass opacities and bilateral infiltrates as the most common CT abnormalities in those with mild or asymptomatic disease while all those with critical disease had diffuse ground-glass opacities with subpleural involvement and pleural effusion. These abnormal findings were present in 89% of patients, 8.9% of whom were asymptomatic at the time of imaging [53] , [54] . Abnormal chest X-Ray findings include bilateral pneumonia (57.9%), unilateral pneumonia (20%) and multiple patchy pulmonary infiltrates (22.7%) [46] )…”
Section: Clinical Features Of Covid-19mentioning
confidence: 99%
“…A meta-analysis of 42 studies of pregnant patients found focal ground glass opacities and bilateral infiltrates as the most common CT abnormalities in those with mild or asymptomatic disease while all those with critical disease had diffuse ground-glass opacities with subpleural involvement and pleural effusion. These abnormal findings were present in 89% of patients, 8.9% of whom were asymptomatic at the time of imaging [53] , [54] . Abnormal chest X-Ray findings include bilateral pneumonia (57.9%), unilateral pneumonia (20%) and multiple patchy pulmonary infiltrates (22.7%) [46] )…”
Section: Clinical Features Of Covid-19mentioning
confidence: 99%
“…Pregnant women with COVID-19 manifested fewer symptoms than general population while the predominant features of symptomatic COVID-19 in pregnant women were cough (33%) and fever (29%). Compared to non-pregnant women with COVID-19 pregnant women were less likely to report fever (OR = 0.48 CI: 0.22-0.85) and myalgia (OR = 0.48 CI: 0.45-0.51) [1,2].…”
Section: Clinical Manifestation Of Covid-19 Infection In Pregnancymentioning
confidence: 95%
“…SARS-CoV-2 is very sensitive for wide array of disinfection products and chemical inactivators [2]. Bilal et al [15] tested hospital rooms and bathrooms in 15 different locations occupied by COVID-19 patients revealing 87% and 60% positive samples, respectively.…”
Section: Transmission Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Boushra et al found that pregnant women are at the highest risk of critical outcome needing intensive care admission or mechanical ventilation during their third trimester. This puts the foetus at a risk of miscarriage, foetal growth restriction, or even prematurity [ 66 ]. In the study conducted by Kotlyar et al , the risk of vertical transmission during the third trimester was found to be 3.2% [ 67 ].…”
Section: Clinical Findingsmentioning
confidence: 99%